2019
DOI: 10.1038/s41526-019-0069-0
|View full text |Cite
|
Sign up to set email alerts
|

Local sleep-like events during wakefulness and their relationship to decreased alertness in astronauts on ISS

Abstract: Adequate sleep quantity and quality is required to maintain vigilance, cognitive and learning processes. A decrease of sleep quantity preflight and on the International Space Station (ISS) has been reported. Recent counter-measures have been implemented to better regulate sleep opportunities on ISS. In our study, astronauts were allocated enough time for sleep the night before the recordings. However, for proper sleep recovery, the quality of sleep is also critical. Unfortunately, data on sleep quality have ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…Some technologies are readily commercially available that are lightweight, highly mobile, battery-operated, and allow non-invasive recordings of electrical cortical activity ( Amaral et al, 2017 ; Casson, 2019 ; He et al, 2019 ). EEG recordings in orbit have been successfully employed as part of the Shuttle mission ‘Neurolab’ ( Witten, 2005 ) and the experiment ‘NeuroSpat’ on the ISS ( Cheron et al, 2006 , 2014 ; Cebolla et al, 2016 ; Petit et al, 2019 ). Weightlessness induces a considerable fluid shift to the upper body ( Thornton et al, 1987 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some technologies are readily commercially available that are lightweight, highly mobile, battery-operated, and allow non-invasive recordings of electrical cortical activity ( Amaral et al, 2017 ; Casson, 2019 ; He et al, 2019 ). EEG recordings in orbit have been successfully employed as part of the Shuttle mission ‘Neurolab’ ( Witten, 2005 ) and the experiment ‘NeuroSpat’ on the ISS ( Cheron et al, 2006 , 2014 ; Cebolla et al, 2016 ; Petit et al, 2019 ). Weightlessness induces a considerable fluid shift to the upper body ( Thornton et al, 1987 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, two separate studies aboard the Space Shuttle (of three and five astronauts) found that crewmembers experienced impaired performance during spaceflight, changes which the authors attributed to fatigue and sleep loss among the crew 3 , 10 . More recent evidence of performance impairment during spaceflight suggest that such changes may relate to a global increase in local sleep-like events during spaceflight compared to on Earth 9 , providing evidence for a relationship between sleep deficiency and performance impairment during spaceflight. Although our data were collected in a spaceflight analogue environment, they suggest that sleep loss during future space missions can be expected to impair performance even among a rigorously selected crew.…”
Section: Discussionmentioning
confidence: 99%
“…One recent study conducted on the ISS investigated sleep events during wake (Petit et al, 2019). EEG was not recorded during sleep, but, interestingly, they found that the astronauts involved in a docking simulation task presented increased global theta EEG oscillations while in space than on Earth, and that this increment was associated with slower reaction times.…”
Section: Stickgold and Hobson 1999mentioning
confidence: 99%